Theoretical and methodological considerations of myth as a way of understanding and integrating culture - Ramírez Angarita, Claudio; Santos, Cristhian Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Duality, seen from a history of eurocentric philosophy between mythical rationality and philosophical rationality, marks an important point in the development of Western thought and its effects on other ways of looking at the world. This situation, which has been proposed among the ancients, takes shape in Latin America and in all political-pedagogical institutions in charge of training subjects of history, where philosophy is understood as cultural production denouncing the cover-up of others. This text provides an analysis of the main characteristics of a myth not only as the background of philosophical and then scientific rationality, but as a constituent element thereof. In other words, it does not disappear; on the contrary, it coexists. Likewise, from a dialectical reading, it is intended to vindicate the mythical rationality on which the explanation of its concrete historical and cultural reality was based, having as reference the Five Element theory and the analogy presented in Native cultures. At the conclusion, a practical exemplification of the foregoing is presented.